Predictors and outcomes of adolescent alcohol and drug use: a scoping review - Mc Carthy, Noel; Smyth, Bobby; Nixon, Elizabeth (Oxford Academic, 2024)
Background: Adolescence is a pivotal life stage marked by educational advancement, entry into the workforce and formation of lasting relationships. Globally, adolescence is also the peak period during which individuals first engage in alcohol and/or drug consumption. This scoping review aimed to summarize existing longitudinal research on factors and outcomes related to adolescent substance use to identify gaps in existing evidence. Methods: A scoping review was conducted in accordance with the PRISMA extension for scoping reviews. A systematic literature search was conducted on PubMed. Additional studies were identified through hand-searching key reference lists and Google Scholar searches. A narrative synthesis was completed. Results: 123 studies were included; 12 reviews and 111 cohort studies. 60% of cohort studies originated from North America, 29% Europe, 7% Australia/New Zealand, 2% South America and 2% Asia. Factors consistently associated with increased risk of ASU include male sex, increasing age, externalizing disorders, adverse childhood experiences and peer or parental substance use. Few studies considered wider community or neighbourhood factors. Early initiation and higher frequency of adolescent drug use were predictive of later- life substance use patterns, education derailment, contact with the justice system and mental health disorders. Conclusions: The body of longitudinal evidence on adolescent substance use is rapidly expanding yet significant research gaps exist. Rising levels of cocaine use and its substantial health impacts motivate further research on all potentially important factors associated with cocaine use to guide interventions for prevention and treatment.
European Journal of Public Health
European Public Health Conference
PUBLISHED
Lisbon